2021
DOI: 10.1002/htj.22425
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of sinusoidal and non‐sinusoidal two‐frequency internal heat modulation in a Rayleigh‐Bénard system

Abstract: A linear stability analysis is assented to investigate the effect of two‐frequency internal heat modulation at the onset of convection in a Newtonian liquid. The correction Rayleigh number and wave number for small amplitudes is calculated using the Venezian approach. Under two‐frequency internal heat modulation, the motion is found to be subcritical. To quantify heat transfer in the system, the three‐mode Lorenz model is solved numerically. Various combinations of sinusoidal and non‐sinusoidal waveforms influ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Mathew and Pranesh 45 ( χ = 0) The sawtooth waveform is the most stabilizing, while the square waveform is the least stabilizing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mathew and Pranesh 45 ( χ = 0) The sawtooth waveform is the most stabilizing, while the square waveform is the least stabilizing.…”
Section: Discussionmentioning
confidence: 99%
“…The study by Noor et al 44 sheds light on the impact of sinusoidal and non‐sinusoidal internal heat modulation on RBC in a viscoelastic fluid. Recently, a similar study was carried out by Mathew and Pranesh 45 in the Newtonian fluid by considering two‐frequency internal heat modulation. They used the Venezian technique to perform a linear stability analysis and concluded that the two‐frequency internal heat modulation destabilizes the system.…”
Section: Introductionmentioning
confidence: 91%